PENYELESAIAN KREDIT MACET PERBANKAN DALAM PANDANGAN ISLAM: Tinjauan Regulasi Kasus Kredit Macet akibat Bencana Alam - Adlan, M. Aqim (An-Nisbah: Jurnal Ekonomi Syariah, 2016)
The existence of bank (Islamic and conventional) as an intermediary financial institution whose existence and operations are regulated by a set of rules and regulations often experiences the uncertainity in taking decisions related to bad loans caused by natural disasters. Like a coin, one hand there are the interests of the owners of capital and the other side there is a sense of humanity toÂ reditors. It is certain that the settlement efforts should involve the appropriate authorities and require a long time. The taken Decisions often differs from the real cases. It looks not giving the sense of justice for creditors.Keywords: Bad Loans, Regulations, and Islam.